2019
DOI: 10.1055/a-0960-0939
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Overweight, Inflammation and Neurological Consequences for the Preterm Child: Results of the ELGAN Study

Abstract: Maternal overweight and obesity are prenatal risk factors for obstetrical complications, preterm birth, neonatal morbidity as well as cognitive and behavioural developmental disorders in children. Paediatric morbidity and mortality as well as child development disorders are significantly associated with maternal obesity. Particularly in the neurodevelopmental and psychiatric area, it is becoming increasingly clear that, in children of mothers with an increased body mass index (BMI), there is a high correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
(154 reference statements)
0
2
0
Order By: Relevance
“…16 This may probably be modulated by epigenetic mechanisms due to circulating cytokines that are particularly elevated in obese pregnant women. 17,25 Conversely, high consumption of fruit, vegetables, nuts, legumes, low-fat dairy products, whole grains, and a low consumption of sodium, sweetened beverages, and red and processed meats, have been reported to have a potential role in controlling high blood pressure during pregnancy. 26 Under certain circumstances, the Mediterranean diet may have a protective effect against oxidative stress 27 and some authors have reported that a Mediterranean-type diet was associated with a lower risk of preterm delivery 28 while others did not find such an association.…”
Section: Discussionmentioning
confidence: 99%
“…16 This may probably be modulated by epigenetic mechanisms due to circulating cytokines that are particularly elevated in obese pregnant women. 17,25 Conversely, high consumption of fruit, vegetables, nuts, legumes, low-fat dairy products, whole grains, and a low consumption of sodium, sweetened beverages, and red and processed meats, have been reported to have a potential role in controlling high blood pressure during pregnancy. 26 Under certain circumstances, the Mediterranean diet may have a protective effect against oxidative stress 27 and some authors have reported that a Mediterranean-type diet was associated with a lower risk of preterm delivery 28 while others did not find such an association.…”
Section: Discussionmentioning
confidence: 99%
“…Poor neurological development of preterm infants is related to delivery weeks ( 1 , 2 ), fetal growth restriction ( 3 , 4 ), chorioamnionitis, maternal infection ( 5 ), maternal increased body mass index (BMI) ( 6 ), socioeconomic disadvantage ( 7 , 8 ), not receiving breast milk at discharge ( 7 ), neonatal intensive care unit (NICU) noise ( 9 ), longer intensive care unit stay, more complex forms of congenital heart disease ( 8 ), and maternal preeclampsia (PE) ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%